On the Convective Motion of Conducting Fluid in Magnetic Field - Zuikan, Ngo (Engineering Transactions, 1985)
The problem of convection in a conducting, viscous and incompressible liquid subject to a magnetic field is considered. The uniqueness theorem is proved and the: structure of the fluctuation spectrum is. determined. ff is proved that the action of the magnetic field increases the stability of motion of the non-uniformly heated, conducting, viscous and incompressible liquid. This conclusion complies with the experimental and numerical results concerning the behaviour of a horizontal layer of liquid.